The contribution of Slovenian biogas plants to the reduction of agricultural sector green house emissions - Romana MARINŠEK LOGAR; Neža NOVAK; Maša VODOVNIK (Acta Agriculturae Slovenica)
Agriculture is a source of emissions of the greenhouse gas methane into the environment. These emissions can be reduced by appropriate storage of animal slurry and manure, with proper fertilization and processing of organic agricultural waste into biogas, where methane is captured and used as an energy source. Biogas is a renewable source of energy that is produced by microbial anaerobic digestion in biogas plants. As a substrate in biogas plants using different types of organic biomass such as animal manure and slurry, crop residues, spoilt silage, waste from food processing industry and biodegradable industrial and municipal waste. Biogas can be used to produce heat and electricity or purified to biomethane as a fuel for vehicles. Digestate can be used as a high-quality fertilizer. Biogas as a renewable energy source represents a replacement for fossil fuels, thus reducing greenhouse gas emissions from fossil sources. The system of financial supports for electricity produced from biogas is applied in Slovenia. There were 24 operating biogas plants in Slovenia in year 2014. Slovenian biogas plants currently produce the majority of biogas from energy crops. As only the minority of biogas is produced from animal excrements we will primarily support the development of agricultural microbiogas plants that will use animal excrements and organic waste biomass from agri-food sector as substrates.